Effect of substituted concentration on structure and magnetic properties of Y3Fe5-xInxO12 - Vu, Thi Hoai Huong (H. : ĐHQGHN, 2019)
This study examines the effect of substituted concentration on the structure and magnetic properties of Y3Fe5-xInxO12 (x = 0.1 ÷ 0.7) powder samples prepared using the sol-gel method. The morphological properties of the samples were analysed using XRD, SEM. The single phase of garnet was obtained in x = 0.1 ÷ 0.6 samples. The lattice parameters of the samples exhibit a linear increase with the increasing In3+ content, which can be explained by a substitution of In3+ ions for Fe3+ ions, considering the larger ionic radius of In3+ compared with that of Fe3+. Crystallite sizes were determined via the XRD data which are of 38 – 49 nm while the particle sizes were estimated from SEM images to be in range of 50 - 100 nm. Magnetization and Curie temperature of the single phase samples were studied by magnetization curves in fields up to 10 kOe and in the temperature range from 80 K to 560K. With the increase of In3+, the magnetization gradually increases while the Curie temperature decreases due to the occupation of In atoms at the a sites and the reduction of intersublattice interaction, respectively.